2020
DOI: 10.1126/sciadv.aax0069
|View full text |Cite
|
Sign up to set email alerts
|

The hypertrophic cardiomyopathy mutations R403Q and R663H increase the number of myosin heads available to interact with actin

Abstract: Hypertrophic cardiomyopathy (HCM) mutations in β-cardiac myosin and myosin binding protein-C (MyBP-C) lead to hypercontractility of the heart, an early hallmark of HCM. We show that hypercontractility caused by the HCM-causing mutation R663H cannot be explained by changes in fundamental myosin contractile parameters, much like the HCM-causing mutation R403Q. Using enzymatic assays with purified human β-cardiac myosin, we provide evidence that both mutations cause hypercontractility by increasing the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 53 publications
(88 reference statements)
15
103
0
Order By: Relevance
“…4). This is consistent with the behavior observed in purified myosin and muscle fibers containing the myosin R403Q mutation (13,41). Interestingly, unlike WT, the SRX population in STFs made of R403Q myosin was insensitive to both the ionic strength and ADP chase.…”
Section: Discussionsupporting
confidence: 87%
“…4). This is consistent with the behavior observed in purified myosin and muscle fibers containing the myosin R403Q mutation (13,41). Interestingly, unlike WT, the SRX population in STFs made of R403Q myosin was insensitive to both the ionic strength and ADP chase.…”
Section: Discussionsupporting
confidence: 87%
“…This increases the number of heads available for binding to actin, which we hypothesized would increase force production. We have measured similar changes in SRX across a range of HCM-causing mutations [8,14], and others have confirmed these effects in cellular and animal models [13,47], suggesting that SRX regulation may be a major cause of hypercontractility in HCM. This is further corroborated by the finding that mavacamten, a small-molecule inhibitor of myosin that is known to increase the SRX state, is effective in reducing symptoms in patients with HCM [13,48].…”
Section: Discussionsupporting
confidence: 67%
“…It was first reported in a study with skinned cardiac muscle fibers that homozygous but not heterozygous MyBPC knockout mice have a significant decrease of the myosin population in the SRX state as compared to WT ( McNamara et al, 2016 ). Consistent with this top-down observation, a bottom-up approach with purified human β-cardiac myosin recently demonstrated that the population of myosin in the SRX state increased in the presence of the C0-C7 MyBPC fragment ( Sarkar et al, 2020 ). Both these studies suggest that MyBPC increases the population of the myosin in the SRX state.…”
Section: Muscle Physiology and The Myosin Srx Statesupporting
confidence: 55%
“…A follow-up study by Adhikari et al, 2019 demonstrated the depopulation of the SRX state in recombinant human β-cardiac myosin constructs harboring mutations in the myosin mesa (R249Q, H251N) and converter (D382Y, R719W) hotspots of HCM mutations in myosin. Sarkar et al, 2020 most recently reported depopulated SRX state in recombinant human β-cardiac myosin harboring the R403Q and R663H mutations, thus extending the Anderson et al, 2018 fiber work.…”
Section: Diseased State and Therapeutic Modulators Of Myosin Srx Statmentioning
confidence: 97%